Tree Insurance-An Innovative Intervention in Industrial Agroforestry - Parthiban, K. T. (Indian Forester, 2016)
The Forest College and Research Institute of Tamil Nadu Agricultural University has implemented a project on "A Value Chain on Industrial Agroforestry in Tamil Nadu" funded by ICAR, NAIP through a consortium mode involving research organizations, wood based industries, tree growing farmers and financial institutions. Through this consortium approach high yielding short rotation varieties in Casuarina, Eucalyptus, Melia, Subabul, Gmelina, Ailanthus and Dalbergia sissoo have been promoted and this has witnessed increased wood production (150 ton/ha) and reduction in rotation (3-5 Years). These activities have attracted several farmers towards tree husbandry and over 45000 ha. have been planted during the last 6 years in association with all stake holders. This successful industrial agroforestry plantations have experienced problem through cyclone and damages due to wild animals which necessitated development of comprehensive tree insurance programme to benefit the farmers. Hence the research group lead by the current author has conceived a comprehensive insurance plan in association with United India Insurance, Chennai and the same is introduced and implemented in Tamil Nadu which attracted over 5000 acres of plantation insurance. This tree insurance model can be extended to the rest of the Country through participation of all stake holders which will ensure protection of farm grown trees against all through abiotic and biotic damages and also protect the farmer's economic benefits. This tree insurance model may be an effective tool for legal security of agroforestry species for ravening farmers in India.